Characteristics of velopharyngeal dysfunction in 22q11.2 deletion syndrome: a retrospective case-control study - Sebastiano Failla; Peng You; Chandheeb Rajakumar; Anne Dworschak-Stokan; Philip C. Doyle; Murad Husein (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objective To identify and describe the dynamic features of velopharyngeal dysfunction (VPD) in patients with 22q11.2 deletion syndrome relative to patients with non-syndromic cleft palates. Study design Retrospective case-control study. Setting Pediatric tertiary care center. Subjects and methods A total of 30 children (aged 9–16 years) with VPD were included in this study. Fifteen children with a definitive diagnosis of 22q11.2 deletion syndrome requiring surgical VPD repair were included in the 22q11.2 deletion syndrome group. Fifteen age- and sex-matched children with non-syndromic cleft palate requiring surgical VPD repair were included in the non-syndromic cleft palate group for comparison. Velar displacement, lateral pharyngeal wall displacement, and lateral pharyngeal wall motion pattern data were extracted from preoperative Multiview Videofluoroscopy imaging studies of all children and compared across groups. Results Lateral pharyngeal wall displacement was found to be reduced in the 22q11.2 deletion syndrome group (U = 29.50, p = .001, r = .63). However, measures of velar displacement were not observed to differ between groups. Similarly, lateral pharyngeal wall motion pattern distributions were not found to differ across these two groups. Conclusions Velopharyngeal dysfunction in patients with 22q11.2 deletion syndrome showed differences in dynamic velopharyngeal function when compared to non-syndromic cleft palate patients. The current findings provide initial insights into the unique aspects of velopharyngeal dysfunction for patients with 22q11.2 deletion syndrome. These findings may guide further efforts directed toward understanding the dynamic velopharyngeal characteristics of this population and potentially optimize surgical management and functional outcomes.